Pertanian Ramah Lingkungan Dengan Pemanfaatan Limbah Rumah Tangga Sebagai Bahan Alami Pada Pupuk Organik Cair - Wahyono, Eko; Ummatin, Binti Nasikhatul; Qur’aini, Ega Fitri; Rochmi, Widya (Abdi Panca Marga, 2022)
The use of chemical-based fertilizers is increasingly found in agriculture, the chemical content in fertilizers will become dangerous if the longer it is used, such as mixing food with chemicals that cause food to become unhealthy, and also the threat of damage to the ecosystem on the ground if Chemical fertilizers are continuously used, this of course becomes a complex problem if allowed to drag on, responding to this, KKN Panca Marga students in Jatiadi Village made observations regarding this matter and then provided a problem solving or problem solving in the form of making liquid organic fertilizer based on household waste in the form of used rice washing water combined with other ingredients that function to replace chemical fertilizers to fertilize plants, this is one of the main work programs carried out by the Jatiadi village community service group which is carried out by providing counseling or socialization si to the residents of the village of Jatiadi in this case the farmer groups in the village of Jatiadi. Keywords: Agriculture,Natural,Fertilizer,Household Waste,